Characterization of the Hewitt Lake and Leta Arm groups, Indin Lake Greenstone Belt, Northwest Territories - Sekhula, Tshepiso Moipane (My University, 2025)
Exposures of the Leta Arm (LA) group and southwestern Hewitt Lake (HL) group volcanic rocks in the northeast-trending 2670-2629 Ma Indin Lake Supracrustal Belt (ILSB) of the western Slave Craton were studied to understand their composition, petrogenesis and tectonic setting. This was achieved by integrating petrology, mineral chemistry, whole-rock geochemistry, U-Pb zircon geochronology, and Sm/Nd isotope analyses. Samples were collected through a combination of surface geological mapping and sampling of historic drill core from different lithologies within the central ILSB volcanic rocks. The ≤2670 Ma HL group is amphibole-rich and comprises mafic and intermediate rocks of basaltic and andesitic composition whereas the 2668-2673 Ma LA group is pyroxene-rich and contains mafic through felsic units ranging from basalt to rhyolite. Alteration was mainly the result of metamorphic processes based on the abundance of ferro-hornblende, actinolite, carbonates, sericite, epidote and minor biotite, quartz, rutile and Fe-Ti oxides. Metamorphic conditions vary from greenschist to amphibolite facies and revealed an interplay of prograde and minor retrograde metamorphism based on amphibole chemistry and the textural relations with primary phases in the rocks. Metamorphism was regional and accompanied by plastic deformation resulting in the formation of high temperature microstructures. Mafic tholeiites of the western HL and LA groups likely formed in an oceanic plateau based on their flat REE on primitive mantle-normalized spider plots, positive to minor Nb anomalies and low La/SmN values of <2. The eastern LA group basalts and felsic to intermediate rocks are characterized by LREE enrichment (La/SmN up to 5.47), positive Th anomalies, negative Ti and Nb anomalies as well as both positive and negative Zr-Hf anomalies. These characteristics are typical of arc-type rocks formed by metasomatism of a mantle wedge above a subducting slab. Low Gd/YbN values < 2.80 in both groups suggest melting at shallow depths in the absence of garnet, possibly suggesting an oceanic rather than continental arc setting. Positive ƐNd values suggest that the rocks did not interact significantly with older crust. The variable negative Nb anomalies in the arc rocks could be the result of crustal contamination or a subduction zone signature as slab-derived fluids stabilize Nb-bearing phases in the slab, leading to depletions of Nb in the metasomatized mantle. The Coterill tonalites may have been the source of contamination and the broadly similar age to the volcanic rocks would allow for modification of the whole rock signature without modifying the isotopic make-up of the LA and HL rocks. Data from this study was used to revise the existing tectonic model for the ILSB volcanic rocks. The new model places the initial formation of the western basalts in an oceanic plateau which collided with a west-moving crustal block and clogged the subduction zone due to its buoyant nature with a new subductions zone forming behind the plateau. Arc magmas from the subducting slab erupted through and onto the plateau to form primitive arc tholeiites and the intermediate to felsic rocks observed in the ILSB.